Construction of asymptotic in Krylov-Bogoliubov-Mitropolsky sense solution of wave equations - Mitropolsky, Yu. A. (Vietnam Journal of Mechanics, 2007)
The paper in question gives consideration to two examples of KBM method for constructing approximate solutions of Klein-Gordon-Bretherton equations often occurred in practice